Materinstvo in materialnost - Trdina, Andreja (Annales. Series historia et sociologia, 2018)
The article investigates maternal practices as class practices and the role of consumption during motherhood and addresses the practices and tastes of mothers in the context of the construction and reproduction of class differences in society. We define class as an interaction achievement and we assume that maternal practices are nowadays together with other practices of everyday life closely intertwined in the creation of distinctions and, thus, in social differentiation. The article is based on in-depth interviews with mothers on various social positions and with different amount of acquired cultural capital in order to sketch differences in class practices of motherhood and to illustrate how through everyday concerns, choices and practices that specifically relate to maternity, symbolic differentiation is produced. In an empirical study, with a comparison between material and formal aesthetics, the demonstration of materialism and idealism, and the local and cosmopolitan taste, we illustrate how differences in cultural capital of informants/mothers structure their patterns of tastes. In general, we find out that mothers with young children belonging to different social classes, have different patterns of social taste and cultural consumption, what is reflected also in their different lifestyles. With concrete examples we highlight how, in the time of early motherhood, class differences are reproduced in everyday life and, above all, through everyday consumer choices, and we recognize the significance of maternity practices as an important field for the construction and maintenance of class divisions.
Keywords: Consumption; Cultural capital; Družbeni razredi; Kulturni kapital; Materinstvo; Motherhood; Okus; Potrošnja; Social classes; Taste